"Krokodil"—A Menace Slowly Spreading Across the Atlantic. (May 2015) - Oliver, Tony; Gheevarghese, Santhosh J.; Gandhi, Umesh; Bhat, Zeenat Y.; Pillai, Unnikrishnan
Abstract : Krokodil (also known as crocodile, croc, krok, and poor man's heroin) is a suspension of desomorphine as the core substance with contaminants like iodide, phosphorous, and heavy metals, which are the byproducts of the manufacturing process. The name krokodil emerged due to the appearance of the skin lesions around the injection site, where it turns green and scaly like a crocodile skin due to desquamation. It is also known as the "drug that eats junkies" and "Russia's Designer drug." It is not available as a prescription anywhere in the world. It is a modern day man-made Frankenstein-like drug, which was manufactured due to the pursuit of drug addicts to make a cheap yet effective narcotic but ended up in creating havoc on its users. It has devastating effects on its users, including damage to skin, blood vessels, muscles, bones, and sometimes even multiorgan failure and eventually death. A systemic review was conducted to obtain any available data for the term krokodil to collect information for this article.